ASPEK HUKUM KEGIATAN WISATA RUANG ANGKASA (SPACE TOURISM) MENURUT HUKUM INTERNASIONAL - Yuliantiningsih, Aryuni (Faculty of Law, Universitas Jenderal Soedirman, 2011)
The activities of States in the exploration and use of outer space began since Uni Sovyet was launching Sputnik sattelite at 1957 and than followed the first manned spaceflight launched namely Yuri Gagarin at 1961. In their activities, manned spaceflight get law protection according Space Treaty and Rescue Agrement. Article 5 Space Treaty regulate that State Parties to the treaty shall regard astonauts as envoys of mankind in outer space and shall render to them all possible assistance in the event of accident, distress, or emergency landing of another State Party. In the other side, the activities of commercial use of outer space is developing, the one is space tourism. This matter not yet be regulated so if there are many problems about the law protection of space tourists and the activities of outer space that performed by private enterprises, the treaties of outer space can be applicated. Key word : space tourism, outer space treaty